Multiphoton luminescent graphene quantum dots for in vivo tracking of human adipose-derived stem cells. Issue 16 (12th April 2016) - Kim, Jin; Song, Sung Ho; Jin, Yoonhee; Park, Hyun-Ji; Yoon, Hyewon; Jeon, Seokwoo; Cho, Seung-Woo
Abstract : The applicability of graphene quantum dots (GQDs) for the in vitro and in vivo live imaging and tracking of different types of human stem cells is investigated. Abstract : The applicability of graphene quantum dots (GQDs) for the in vitro and in vivo live imaging and tracking of different types of human stem cells is investigated. GQDs synthesized by the modified graphite intercalated compound method show efficient cellular uptake with improved biocompatibility and highly sensitive optical properties, indicating their feasibility as a bio-imaging probe for stem cell therapy.